2021
DOI: 10.1073/pnas.2110995118
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated peptide chains at the fibril tip control the kinetics of growth of amyloid-β fibrils

Abstract: Amyloid fibrillization is an exceedingly complex process in which incoming peptide chains bind to the fibril while concertedly folding. The coupling between folding and binding is not fully understood. We explore the molecular pathways of association of Aβ40 monomers to fibril tips by combining time-resolved in situ scanning probe microscopy with molecular modeling. The comparison between experimental and simulation results shows that a complex supported by nonnative contacts is present in the equilibrium stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…Both CsgA and FapC show a log-linear relationship between elongation rate constants and [urea] between 0 and 8 M urea [63]. This rules out detectable intermediates during FuBA elongation, in contrast to Aβ1-40, which was recently proposed to go through a "frustrated" complex intermediate [82]. This is manifested as in increase in the elongation rate of Aβ up to 1.5 M urea [82], after which there is a decrease in the elongation rate, as described by other groups for both Aβ1-40 and Aβ1-42 [79,80].…”
Section: Probing Fuba Fibrillation As Folding Steps With Denaturants:...mentioning
confidence: 65%
See 1 more Smart Citation
“…Both CsgA and FapC show a log-linear relationship between elongation rate constants and [urea] between 0 and 8 M urea [63]. This rules out detectable intermediates during FuBA elongation, in contrast to Aβ1-40, which was recently proposed to go through a "frustrated" complex intermediate [82]. This is manifested as in increase in the elongation rate of Aβ up to 1.5 M urea [82], after which there is a decrease in the elongation rate, as described by other groups for both Aβ1-40 and Aβ1-42 [79,80].…”
Section: Probing Fuba Fibrillation As Folding Steps With Denaturants:...mentioning
confidence: 65%
“…This rules out detectable intermediates during FuBA elongation, in contrast to Aβ1-40, which was recently proposed to go through a "frustrated" complex intermediate [82]. This is manifested as in increase in the elongation rate of Aβ up to 1.5 M urea [82], after which there is a decrease in the elongation rate, as described by other groups for both Aβ1-40 and Aβ1-42 [79,80]. For globular proteins, an increase in folding rate with [denaturant] at low [denaturant] is evidence of an off-pathway species which has to unfold back to the denatured state for folding to proceed [83,84].…”
Section: Probing Fuba Fibrillation As Folding Steps With Denaturants:...mentioning
confidence: 74%
“…In addition, however, we find another species with many interchain parallel hydrogen bonds. In this class, the number of interchain hydrogen bonds is more than for the disordered species but is fewer than for the fully ordered prefibrillar species, which are also found in Aβ aggregation . These species, which we call prefibrillar oligomers with disordered tips, are dominated by fibril-like β sheet chains with the addition of a few β hairpin chains at the ends.…”
Section: Resultsmentioning
confidence: 95%
“…In this class, the number of interchain hydrogen bonds is more than for the disordered species but is fewer than for the fully ordered prefibrillar species, which are also found in Aβ aggregation. 36 These species, which we call prefibrillar oligomers with disordered tips, are dominated by fibril-like β sheet chains with the addition of a few β hairpin chains at the ends. The existence of two kinds of species, the fully ordered prefibrillar oligomers and the prefibrillar oligomers with disordered tips, agrees with FRET experiments which suggest there are two classes of species when the oligomer size is larger than 5.…”
Section: Aggregation Landscapes Of α-Synucleinmentioning
confidence: 99%
“…This would lead to inhibition of the elongation of the former complex but not of the latter complex (Figure S9). Interestingly, a previous study suggested that in the case of fibrils made of two protofilaments, the probability of monomer binding to fibril ends by non-native interactions, leading to retardation of fibril growth, would be high.…”
Section: Resultsmentioning
confidence: 99%